Incidence (1988–97) and prevalence (1997) of multiple sclerosis in Västerbotten County in northern Sweden. Issue 1 (1st January 2003) - Sundström, P; Nyström, L; Forsgren, L
Abstract : Objective: To investigate the incidence and prevalence of multiple sclerosis in Västerbotten County in northern Sweden. Methods: Multiple sources were used in the case identification process. Follow up interviews with clinical examinations were undertaken and, when indicated, additional paraclinical investigations were done. In this way case ascertainment was assured and supplemental clinical data were collected. The incidence rate was based on symptom onset. Onset adjusted prevalence was applied. Results: The crude incidence rate of multiple sclerosis in 1988–97 in Västerbotten County was 5.2/10 5 (95% confidence interval, 4.4 to 6.2): 6.7/10 5 (6.0 to 8.3) in women and 3.7/10 5 (2.7 to 4.9) in men. The onset adjusted prevalence for 31 December 1997 was 154/10 5 (139 to 170): 202/10 5 (179 to 228) in women and 105/10 5 (89 to 125) in men. When compared with a previous estimate of prevalence, a yearly 2.6% increase in prevalence between 1990 and 1997 was found, mainly attributable to a higher incidence than mortality. Conclusions: The present incidence rate and prevalence confirms earlier findings that Västerbotten is a high risk area for multiple sclerosis. The adjusted incidence was twice as high as the incidence from 1974–88 in the only previous Swedish population based study from Göteborg, but comparable with other recent Fennoscandian multiple sclerosis incidence rates.